(untitled) (Indian Journal of Animal Production and Management, 2016)
An extensive survey was carried out to explore the participation of women in Pantja goat rearing in Tarai region of Uttarakhand. The results of study clearly showed that women played a predominant role in goat rearing. A majority of women farmers performed assistance at the time of parturition (73.95%) followed by cleaning of animal shed (61.40%), care of sick animal (56.43%), stall feeding after grazing (54.11%), care of young stock (52.40 %), dusting (54.26%) and grazing of goats (47.44%). In the same tasks the involvement of men was 26.05, 35.04, 42.02, 40.93, 45.89, 45.74 and 46.51 percent whereas, adolescent participated in the above mentioned tasks to the extent of 00.0, 3.57, 1.55, 4.96, 1.71, 0.00 and 6.05 percent. The results of the present study indicated that the women farmers were capable of managing the goats in a similar fashion to men even without any formal training, and their skills could be strengthened by imparting to them proper scientific training (related to goat production technology) suited to the ecosystem of Tarai region of Uttarakhand. It is quite obvious from the observations collected during the survey that there is an urgent need for the policy makers to pay more attention to the involvement of women farmers involved in goat production by enhancing their skills through education provided by the extension workers, voluntary organizations and government agencies. It will not only increase the efficiency of goat production but also elevate the socio economic conditions of the rural masses of the district.